1977
DOI: 10.1111/j.1365-246x.1977.tb03720.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sq current system during the International Geophysical Year

Abstract: The daily variation for the mean of the eight most quiet days of the IGY is represented as a function of latitude, longitude and UT by ~ncaiis of a spherical harmonic model. The most appropriate choice ofS4 baseline is investigated, on the assumption that the external electric currents deduced from the model should be negligible at local midnight. The properties of tlic final model are discussed, particularly with regard to the external current foci, and are compared with those of previous models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 14 publications
4
54
1
Order By: Relevance
“…The difference between the values of the northern and southern foci indicates the total current intensity, which is about 300 kA, for the summer season. This is very high, when compared with the summer current intensities of other global regions (Malin and Gupta, 1977;Campbell and Schiffmacher, 1985). As observed in this study, Malin and Gupta (1977) also have reported a maximum intensity of current for Sq when its focus is located at mid-Pacific.…”
Section: Equivalent Ionospheric Source Current Systemssupporting
confidence: 63%
“…The difference between the values of the northern and southern foci indicates the total current intensity, which is about 300 kA, for the summer season. This is very high, when compared with the summer current intensities of other global regions (Malin and Gupta, 1977;Campbell and Schiffmacher, 1985). As observed in this study, Malin and Gupta (1977) also have reported a maximum intensity of current for Sq when its focus is located at mid-Pacific.…”
Section: Equivalent Ionospheric Source Current Systemssupporting
confidence: 63%
“…In early studies of Sq, the mean (or median) value of the Sq variation was often used as the baseline. Later, however, it was realized that the average of nighttime values of the Sq variation is more physically meaningful because the source currents in the ionosphere effectively vanish during the night (e.g., Price and Wilkins 1963;Malin and Gupta 1977). At altitudes 100-150 km, nighttime Pedersen and Hall conductivities are a few orders of magnitude smaller than daytime values.…”
Section: Determination Of Baselinesmentioning
confidence: 99%
“…Unfortunately, these advances on the theoretical front have not been matched by significant improvements in the quality or frequency range of the electromagnetic response data set. This is not to deny the value of those analyses which have been made, particularly of the periodic and quasi-periodic variations, such as the annual (MALIN and ISIKARA, 1976), eleven-year solar cycle (HARWOOD andMALIN, 1977, DucRuix et al, 1980) and daily variation (MALIN, 1977). Nonetheless, there seems to be a lack of confidence in the data as a whole, judging by the number of inversion attempts which restrict themselves to fitting relatively small subsets.…”
Section: Introductionmentioning
confidence: 99%